"There is no way to avoid the first bite": A qualitative investigation of addictive-like eating in treatment-seeking Brazilian women and men. (1st June 2019) - Lacroix, Emilie; Oliveira, Edgar; Saldanha de Castro, Juliana; Cabral, Janice Rico; Tavares, Hermano; von Ranson, Kristin M.
Abstract: There has been polarizing debate on addictive-like eating in recent years. To move toward valid definition and measurement of this construct, qualitative research describing individuals' experiences is needed. The present study explored how Brazilian men and women define and experience addictive-like eating. Interviews were conducted with 7 men and 8 women ( M age = 46.6 years, M BMI = 35.43 kg/m 2 ) seeking treatment for addictive-like eating. Thematic analysis of interviews identified three saturated, overarching themes describing participants' conceptualizations of the (1) characteristics, (2) causal factors, and (3) consequences of addictive-like eating. Lack of control was a key characteristic of addictive-like eating described by all participants. A causal factor which most participants described was emotional eating. Consequences included emotional, interpersonal, occupational, and health-related impairments which appeared primarily related to weight gain, rather than to the pattern of addictive-like eating itself. These results are largely consistent with those of previous qualitative studies. Importantly, the symptoms described by our participants and in previous qualitative studies may be inadequately captured by existing self-report questionnaires designed to assess addictive-like eating. To address this potential limitation, we provide recommendations for assessing the full range of possible addictive-like eating symptoms.